In vitro growth-inhibitory effect of ethanol GRAS plant and supercritical CO₂ hop extracts on planktonic cultures of oral pathogenic microorganisms - Pilna, J; Vlkova, E; Krofta, K; Nesvadba, V; Rada, V; Kokoska, L (Fitoterapia, 2015)
Conventional chemical antiseptics used for treatment of oral infections often produce side-effects, which restrict their long-term use. Plants are considered as perspective sources of novel natural antiseptics. However, little is still known about their inhibitory properties against oral pathogens. The objective of this study was to test in vitro antimicrobial activities of generally recognized as safe (GRAS) species against planktonic cultures of cariogenic, periodontal and candidal microorganisms and identify active compounds of the most active extracts. Growth-inhibitory effects of ethanol extracts from 109 GRAS plant species, six Humulus lupulus cultivars and two hop supercritical CO2 extracts were evaluated using broth microdilution method. The chemical analysis was done through high-performance liquid chromatography. Best results were obtained for supercritical CO2 and ethanol extracts of H. lupulus with minimum inhibitory concentrations (MIC) ≥8 μg/mL and ≥16 μg/mL, respectively. The chemical analysis of supercritical CO2H. lupulus extracts revealed that α- and β-acids were their main constituents. Capsicum annuum and Capsicum frutescens showed antibacterial effect against Streptococcus sobrinus and Streptococcus salivarius (MIC=64-128 μg/mL). These strains were further inhibited by Zanthoxylum clava-herculis (MIC=64-128 μg/mL) and Myristica fragrans (both MIC≥128 μg/mL). The latter also exhibited antimicrobial activity against Fusobacterium nucleatum (MIC=64 μg/mL). Punica granatum possessed inhibitory effects against Candida albicans (MIC=128 μg/mL) and F. nucleatum (MIC=64 μg/mL). The results indicate that supercritical CO2H. lupulus extracts together with ethanol extracts of C. annuum, C. frutescens, M. fragrans, P. granatum and Z. clava-herculis are promising materials for further investigation on new antiseptic agents of oral care products.
Keywords: Myristica; Candida albicans; Microbial Sensitivity Tests; Candidiasis; Plant Extracts; Microdilution method; Humulus; Capsicum; mikrobiální testy citlivosti; ethanol; rostlinné extrakty; Anti-Bacterial Agents; Humulus lupulus; Periodontal disease; Ethanol; Streptococcus sobrinus; Fusobacterium nucleatum; Zanthoxylum; Antimicrobial activity; antibakteriální látky; Dental caries